Shortage of male teachers. (c2013) - Antar, Rafik (2013)
This study addresses the issue of the predominant shortage in male teachers at the lower grade levels in Lebanese schools. This issue has been highlighted in the international literature for decades, and many studies from Europe and North America have found that young students can benefit from having a male role model and that many males are discouraged from teaching young children due to misconceptions and low salaries. Research on this topic in Lebanon has been scarce, so this study can create awareness of this international and national shortage in male elementary teachers and perhaps help address the causes. In this exploratory study, perceptions of student teachers, retired and current male teachers and school directors were elicited concerning this shortage in male elementary teachers. Questionnaires were distributed to 91 undergraduate and graduate university students enrolled in a department of education at a private higher education institution. Face-to-face interviews were conducted with 2 retired male teachers and one current male teacher, and online interviews were conducted with 5 school directors: two Preschool directors, two Elementary directors, and one vice principal. Qualitative and quantitative data analysis yielded results that were triangulated and used to address the research questions. Findings of this study showed that the salary plays an important role in a male’s choice of career path; however, there were no significant results in terms of the impact of self-image and professional identity in this matter.